Using Active Learning to Identify Health Information Technology Related Patient Safety Events - Fong, Allan; Howe, Jessica L.; Adams, Katharine T.; Ratwani, Raj M. (Applied Clinical Informatics, 2017)
The widespread adoption of health information technology (HIT) has led to new patient safety hazards that are often difficult to identify. Patient safety event reports, which are self-reported descriptions of safety hazards, provide one view of potential HIT-related safety events. However, identifying HIT-related reports can be challenging as they are often categorized under other more predominate clinical categories. This challenge of identifying HIT-related reports is exacerbated by the increasing number and complexity of reports which pose challenges to human annotators that must manually review reports. In this paper, we apply active learning techniques to support classification of patient safety event reports as HIT-related. We evaluated different strategies and demonstrated a 30% increase in average precision of a confirmatory sampling strategy over a baseline no active learning approach after 10 learning iterations.
Keywords: Patient safety; health information technology; active learning; human-in-the-loop; machine learning; patient safety event reports